A systematic review of the effects of upper body warm-up on performance and injury. Issue 14 (18th February 2015) - McCrary, J Matt; Ackermann, Bronwen J; Halaki, Mark
Abstract : Purpose: This systematic review was conducted to identify the impact of upper body warm-up on performance and injury prevention outcomes. Methods: Web of Science, MEDLINE, SPORTDiscus, PsycINFO and Cochrane databases were searched using terms related to upper extremity warm-up. Inclusion criteria were English language randomised controlled trials from peer-reviewed journals in which investigation of upper body warm-up on performance and injury prevention outcomes was a primary aim. Included studies were assessed for methodological quality using the PEDro scale. A wide variety of warm-up modes and outcomes precluded meta-analysis except for one group of studies. The majority of warm-ups were assessed as having 'positive', 'neutral', 'negative' or 'specific' effects on outcomes. Results: Thirty-one studies met the inclusion criteria with 21 rated as having 'good' methodological quality. The studies investigated a total of 25 warm-up modes and 43 outcome factors that could be grouped into eight mode and performance outcome categories. No studies of upper body warm-up effects on injury prevention were discovered. Conclusions: Strong research-based evidence was found for the following: high-load dynamic warm-ups enhance power and strength performance; warm-up swings with a standard weight baseball bat are most effective for enhancing bat speed; short-duration static stretching warm-up has no effect on power outcomes; and passive heating/cooling is a largely ineffective warm-up mode. A clear knowledge gap in upper body warm-up literature is the lack of investigation of injury prevention outcomes.